Supporting science learning in linguistically diverse classrooms: Factors related to the use of bilingual content in a computer-based learning environment - Van Laere, Evelien; Agirdag, Orhan; van Braak, Johan (Computers in human behavior, 2016)
Computer-based learning environments (CBLEs) are a promising means to support language minority (LMi) students in acquiring knowledge and skills through the integration of authentic support in their home language. This study aimed to determine the use of scientific bilingual content offered to fourth-grade students (n = 250) in the CBLE E-Validiv and to identify both student and classroom characteristics related to this use. All the content in E-Validiv is accessible in the language of instruction and one of six other languages. For LMi students, the other language is set to their home language. Multilevel hierarchical regression analyses show that especially LMi students who assess themselves as highly proficient in their home language use the content more in the other language than language majority students. However, even LMi students focus mainly on content in the language of instruction, which indicates that they particularly apply their home language to support their learning process in the language of instruction. Additionally, students who perform higher on science subjects access content more in the language of instruction. The presence of linguistic diversity in the classroom and the positive use of linguistic diversity by the teacher do not seem to matter. The theoretical and practical implications are discussed. •A computer-based learning environment offering bilingual content is presented.•Language minority students access the language of instruction and their home language.•They use their home language particularly as a support for learning.•Proficiency in their home language plays a role in the use of bilingual content.•Higher science achievement is positively related to use of the language of instruction.